2018
DOI: 10.3892/mmr.2018.8878
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of heat shock protein 90 augment endothelin‑1‑induced heat shock protein 27 through the SAPK/JNK signaling pathway in osteoblasts

Abstract: It has been previously reported that endothelin‑1 (ET‑1) stimulates the induction of heat shock protein (HSP) 27 through the activation of p38 mitogen‑activated protein (MAP) kinase and stress‑activated protein kinase/c‑Jun N‑terminal kinase (SAPK/JNK) in osteoblast‑like MC3T3‑E1 cells. The present study investigated whether HSP90, a high‑molecular‑weight HSP, was implicated in the ET‑1‑stimulated HSP27 induction in MC3T3‑E1 cells. The effects of HSP90 inhibitors on the induction of HSP27 were examined. The HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…demonstrated that ATP at low concentrations strongly inhibited bone formation. 21 In addition, previous studies have suggested that changes in HSP, 22,23 carbohydrate metabolism 24 or glycine metabolism-related protein families 25 also disrupt the balance of bone homeostasis. Thus, these densely connected proteins may state novel ideas for thorough research and help to identify new therapeutic agents for NF1 associated with CPT.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that ATP at low concentrations strongly inhibited bone formation. 21 In addition, previous studies have suggested that changes in HSP, 22,23 carbohydrate metabolism 24 or glycine metabolism-related protein families 25 also disrupt the balance of bone homeostasis. Thus, these densely connected proteins may state novel ideas for thorough research and help to identify new therapeutic agents for NF1 associated with CPT.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we reported that PGF 2α or thrombin stimulates the synthesis of IL‐6 via p44/42 MAPK and p38 MAPK in osteoblast‐like MC3T3‐E1 cells, and that Rho‐kinase acts at a point upstream of p38 MAPK in the signalling 22,23 . We have also demonstrated that ET‐1 stimulates the induction of HSP27 via p38 MAPK and JNK, and that BMP‐4 stimulates OPG production via p70 S6 kinase in these cells 24,25 . Additionally, we have shown that TNF‐α stimulates the synthesis of IL‐6 via p44/42 MAPK and PI3K/Akt in MC3T3‐E1 cells, and p70 S6 kinase limits the TNF‐α‐stimulated IL‐6 synthesis at a point upstream of p44/42 MAPK and Akt in MC3T3‐E1 cells 41,42 .…”
Section: Discussionmentioning
confidence: 82%
“…In addition, we demonstrated that HSP90 negatively regulates IL‐6 synthesis stimulated by prostaglandin F 2α (PGF 2α ) or thrombin in these cells 22,23 . We further reported that HSP90 could limit HSP27 expression induced by endothelin‐1 (ET‐1) 24 and positively regulate the bone morphogenetic protein‐4 (BMP‐4)‐stimulated synthesis of osteoprotegerin (OPG), an endogenous suppressor of osteoclastogenesis, in MC3T3‐E1 cells 25 . These results lead us to speculate that HSP90 might play the role of an essential modulator of osteoblast functions.…”
Section: Introductionmentioning
confidence: 93%
“…Hsp27 was also found to regulate lung fibroblast differentiation in response to TGF-b via activation of Smad3 and ERK-MAPK (Wang et al, 2017). Other receptor systems have also been implicated in Hsp27 signaling: These include the membrane-associated androgen receptor (Li et al, 2018) and endothelin-1 stimulation (Fujita et al, 2018). Hsp27 has further been implicated in different physiologic processes downstream of these receptors.…”
Section: Heat Shock Protein 27mentioning
confidence: 99%